Analysis of Acceptance of Mobile JKN Usage using the Utaut Method in the Working Area of BPJS Kesehatan Branch Mataram - I Made Adi Putra Asmara; Saimi Saimi (GLOBAL HEALTH SCIENCE GROUP, 2025)
The low adoption rate of the Mobile JKN application in the operational area of BPJS Kesehatan Mataram Branch represents a major obstacle. The application was developed to improve accessibility and efficiency in digital health services, yet its usage remains low.Objective: This study aims to analyze the factors influencing user acceptance of the Mobile JKN application using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework.Methods:This quantitative study employed a cross-sectional study design. The study population included all users of the Mobile JKN application within the BPJS Kesehatan Mataram Branch operational area, with a sample of 399 respondents selected through simple random sampling. Primary data was gathered using structured questionnaires, while secondary data was sourced from BPJS Kesehatan records. The questionnaire was validated with a significance level (p-value < 0.05) and reliability tested with Cronbach’s Alpha (≥ 0.7). Data analysis was conducted using the Chi-square test for bivariate analysis and regression analysis for multivariate analysis.Results: The results revealed significant relationships between user behavior (use behavior) and performance expectancy (p < 0.001), effort expectancy (p < 0.001), facilitating conditions (p < 0.001), hedonic motivation (p < 0.001), and price value (p < 0.001). However, social influence (p = 0.361) and habit (p = 0.628) were not significantly associated. The results of the multinomial logistic regression test identify that effort expectancy is the dominant factor influencing user behavior.Conclusion: This study concludes that perceived economic value, ease of use, and infrastructure support are critical for enhancing the adoption rate of Mobile JKN. Policymakers need to strengthen user education, simplify the application interface, and enhance technological infrastructure as well as integration with information systems in healthcare facilities to promote broader utilization.